KEKERASAN SIMBOLIK MEDIA MASSA PADA PEMBERITAAN BONEK: CRITICAL DISCOURSE ANALYSIS BERITA MEDIA - , Rangga Agnibaya ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The study entitled "The Symbolic Violence of Mass Media in News about Bonek: Critical Discourse Analysis in News Media" assumes that the discourse contained in news about bonek is socially constructed. Thus, the news is not considered to be value- free. Even, in the construction process, occurs the symbolic violence. The symbolic violence reflects how mass media is against bonek as an object of news. And, the symbolic violence often manifest in the process of marginalization through linguistic elements of news, such as topics, news scheme, and language style. However, this case may also not be separated from the fact that mass media has a symbolic power that put them in a privileged position in the social structure of Indonesian society. In the process of discourse production about bonek, mass media, moreover, is often influenced by certain social cognition, thus, it becomes not value- free. The social cognition then may affect someoneâs perspective on any event (mental model). In the news discourse of bonek, the social cognition is also found. Based on the discourse analysis in this study, it is then known that the social cognition involved is knowledge about the phenomena of fans who are often become synonymous with violence and social illness. In addition, it is also indicated that the media industry paradigm emphasizing on the value of news (news worthy) is also influential in shaping the discourse about bonek in the mass media.